Characteristics of Ti3C2X–Chitosan Films with Enhanced Mechanical Properties - Hu, Chunfeng; Shen, Fei; Zhu, Degui; Zhang, Haibin; Xue, Jianming; Han, Xiaogang (Frontiers in Energy Research, 2017)
Chitosan-reinforced Ti3C2X films were successfully fabricated by infiltrating Ti3C2X suspensions containing different chitosan contents followed by vacuum drying. The designed chitosan contents were 0, 7, 10, and 14 wt%. It was determined that as-prepared films had shell-like nanolaminar microstructure. Displacement of Ti3C2X nanosheets increased from 24.254 Å (0 wt%) to 28.822 Å (10 wt%) and then decreased to 28.132 Å (14 wt%) with increment of chitosan content. Tensile strength of films continuously increased from 8.20 to 43.52 MPa, enhancing 5.3 times. Electrical resistivity of films increased from 0.39 mΩ cm (0 wt%) to 54.91 mΩ cm (14 wt%). Only pure Ti3C2X film could be used as electrode in the sodium battery.